PENYELENGGARAAN PELAYANAN PUBLIK PADA UNIT TERPADU SATU ATAP (UPTSA) KOTA SURABAYA - Chintyawati, Rizky; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to evaluate the performance of public service management on Unit PelayananTerpadu Satu Atap (UPTSA) Kota Surabaya Timur which is located on Jalan Menur no 31C Surabaya. Thisresearch is conducted at UPTSA Kota Surabaya which is a public service institution which is formed by localgovernment of Surabaya to provide fast, easy, and transparent services to public. This research uses qualitativedescriptive research. The determination of informant technique is done by using purposive sampling since thisresearch is intended to seek for in depth information from the people who know a lot about the focus of thisresearch. The informant of this research is the UPTSA officers who have authorities in giving the requiredinformation. The result of this research shows that the performance of UPTSA is in accordance with theindicators which have been stated in the PERMENPAN No 001 of 2015 about the evaluation guideline of publicservice management which includes the standard of public service which has been carried out in accordance withthe prevailing regulations, the service announcement which has been formulated and has been carried outproperly, community satisfaction survey has been conducted periodically in every 6 months, the complaintmanagement is established and carried out properly but it requires improvement and additional of complaintmanagement officer, and public services information system which has been made based on the law but it has notbeen implemented properly so efforts are required in order to implement it in accordance with the prevailingregulationsKeywords: evaluation, performance, public service management